Assessment of microdamage caused by orthodontic miniscrew pilot holes - Jensen Sven W.; Jensen Emilija D.; Sampson Wayne J.; Dreyer Craig W. (Australasian Orthodontic Journal, 2020)
The clinical success of orthodontic miniscrew implants may be improved after pre-drilling a pilot hole. However, the amount of microdamage to the bone surface produced by the pilot hole is largely unknown. The present study aimed to quantify the damage to cortical bone after the creation of a pilot hole.